2018
DOI: 10.3791/57938
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Protocol for Examining Behavioral Response Profiles in Larval Fish: Application to the Neuro-stimulant Caffeine

Abstract: Fish models and behaviors are increasingly used in the biomedical sciences; however, fish have long been the subject of ecological, physiological and toxicological studies. Using automated digital tracking platforms, recent efforts in neuropharmacology are leveraging larval fish locomotor behaviors to identify potential therapeutic targets for novel small molecules. Similar to these efforts, research in the environmental sciences and comparative pharmacology and toxicology is examining various behaviors of fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 34 publications
4
26
0
1
Order By: Relevance
“…Colón‐Cruz et al () showed that naive 6‐dpf fathead minnows, also used in our study, displayed high activity in the light compared with the dark cycles after observations of their photo‐dependent swimming activity. This general light‐to‐dark cycle behavior was identical to that observed in our acute studies and also identified for fathead minnows by Steele et al (; 2018b) after acute 96‐h behavior toxicity studies. In contrast, larval zebrafish display higher activity in the dark than in the light and with less variability (Kristofco et al ; MacPhail et al ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Colón‐Cruz et al () showed that naive 6‐dpf fathead minnows, also used in our study, displayed high activity in the light compared with the dark cycles after observations of their photo‐dependent swimming activity. This general light‐to‐dark cycle behavior was identical to that observed in our acute studies and also identified for fathead minnows by Steele et al (; 2018b) after acute 96‐h behavior toxicity studies. In contrast, larval zebrafish display higher activity in the dark than in the light and with less variability (Kristofco et al ; MacPhail et al ).…”
Section: Discussionsupporting
confidence: 89%
“…The use of zebrafish as a model system for developmental, biomedical, and toxicological research has spurred the need to understand their behavior and has made them the typical model organism studied (MacPhail et al ). Pimephales promelas , on the other hand, have been typically used by US regulatory agencies focused on survival and growth endpoints; however, recent studies have begun to investigate their behavioral sensitivity after contaminant exposures (Colón‐Cruz et al ; Steele et al , 2018b). Colón‐Cruz et al () showed that naive 6‐dpf fathead minnows, also used in our study, displayed high activity in the light compared with the dark cycles after observations of their photo‐dependent swimming activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Xia et al 2018) Danio rerio Neurotoxicants 1 nM to 100 mM Six of the ten tested neurotoxicants provoked developmental neurotoxicity; the triple-transgenic zebrafish line can be used to assess developmental neurotoxicity during neuronal differentiation (Koiwa et al 2019) Danio rerio Caffeine 0.001 mg/L to 186.67 mg/L Caffeine at concentrations above at concentrations !0.039 mg/L significantly altered zebrafish behavior. (Steele, Mole, and Brooks 2018) Danio rerio Coriandrum sativum extract 25, 50 or 100 mg/kg Coriandrum sativum extract presents anxiolytic effects against alarm substance-induced locomotor and anxiogenic responses (Zenki et al 2020) Danio rerio D9-tetrahydrocannabinol (THC) or cannabidiol (CBD) THC (0.08, 0.4, 2 mM) or CBD (0.02, 0.1, 0.5 mM)…”
Section: Resultsmentioning
confidence: 99%
“…Four embryos/larvae were allocated to each replicate of each treatment group (SC and 18.2, 43.4, and 105.9 µg/L BPAP, N = 6), and after 6 min of acclimation, the tracking was continued for four phases, which consisted of two cycles of a 6-min light/6-min dark period for a total of 24 min. Using EthoVision software (Noldus Information Technology, Wageningen, The Netherlands), the distance moved (cm) and moving duration (s, time of moving speed > 0.2 cm/s) were calculated for each individual larvae [ 27 ].…”
Section: Methodsmentioning
confidence: 99%